Method of using innovative technologies in conducting English lessons in schools - Jalalova, Sevara Janabay kizi (Science and Education, 2023)
In this methodological manual, the method of using innovative technologies in conducting English lessons in secondary schools, teaching grammar to elementary and upper classes was highlighted.